2021
DOI: 10.2147/prbm.s298948
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the FCV-19 Scale and Assessment of Fear of COVID-19 in the Population of Mozambique, East Africa

Abstract: This study aimed to validate the Portuguese version of the Fear of COVID-19 Scale (FCV-19S) and investigate its association with sociodemographic and pandemicrelated variables in the population of Mozambique. Participants and Methods: A cross-sectional online survey recruited 387 Mozambicans aged 18 to 70 years. The psychometric properties of the Portuguese version of the FCV-19S were evaluated using confirmatory factor analysis and Rash analysis. Additionally, the association of the FCV-19S with sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
9
10
0
Order By: Relevance
“…The levels of anxiety and fear of the COVID-19 seem to be lower for this age group over 65 (mean = 5.11 ± 1.83) than for the general population, as compared to the data reported by the authors of the AMICO scale in their previous study [ 34 , 35 ], who found mean values of 5.54 (± 1.83) and a range with higher upper limit values (from 1.22 to 10 points). Other studies with older populations also found lower values of fear in older adults than other lower age groups or compared to the general population [ 22 , 23 , 32 , 58 , 59 ], which is corroborated by the meta-analysis by Lin et al [ 36 ] with data from the use of the FCV-19 scale in eleven studies from different countries and general population samples of different ages. In this sense, another work with samples of older people [ 60 ] reports relatively lower values of fear of COVID-19 than in the general population in the same context, based on FCV-19 scale measures [ 61 ], with no differences between age groups above 65 years (65–74, 75–85, and 85–94 years).…”
Section: Discussionsupporting
confidence: 56%
“…The levels of anxiety and fear of the COVID-19 seem to be lower for this age group over 65 (mean = 5.11 ± 1.83) than for the general population, as compared to the data reported by the authors of the AMICO scale in their previous study [ 34 , 35 ], who found mean values of 5.54 (± 1.83) and a range with higher upper limit values (from 1.22 to 10 points). Other studies with older populations also found lower values of fear in older adults than other lower age groups or compared to the general population [ 22 , 23 , 32 , 58 , 59 ], which is corroborated by the meta-analysis by Lin et al [ 36 ] with data from the use of the FCV-19 scale in eleven studies from different countries and general population samples of different ages. In this sense, another work with samples of older people [ 60 ] reports relatively lower values of fear of COVID-19 than in the general population in the same context, based on FCV-19 scale measures [ 61 ], with no differences between age groups above 65 years (65–74, 75–85, and 85–94 years).…”
Section: Discussionsupporting
confidence: 56%
“…In spite of the FCV-19S being unidimensional, there is a pattern of response to the items where endorsements of items 3, 6 and 7 are comparatively low when contrasted with the scores of the remaining items. The pattern was observed in mean scores reported by studies such as Elemo et al (2020), Giordani et al (2021), Pang et al (2020), Perz et al (2020), Sakib et al (2020), Satici et al (2020), Soraci et al (2020) and Winter et al (2020). A closer inspection of the items shows that they refer to physiological reactions because of COVID-19 fear (Alyami et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…To this end, Ahorsu et al (2020) developed a seven-item Fear of COVID-19 scale (FCV-19S) to evaluate anxiety specific to COVID-19, based on the protection motivation theory (Rogers, 1975). The measure has been translated into a number of languages and validated in a number of countries including Bangladesh (Sakib et al, 2020), China (Chi et al, 2021), Ethiopia (Elemo, Satici, & Griffiths, 2020), France (Mailliez, Griffiths, & Carre, 2020), Greece (Tsipropoulou et al, 2020), Israel (Bitan et al, 2020), Italy (Soraci et al, 2020), Japan (Masuyama, Shinkawa, & Kubo, 2020) Malaysia (Pang et al, 2020), Mozambique (Giordani, Giolo, Muhl, Estavela, & Gove, 2021), New Zealand (Winter et al, 2020), Russia (Reznik, Gritsenko, Konstantinov, Khamenka, & Isralowitz, 2020), Saudi Arabia (Alyami, Henning, Krägeloh, & Alyami, 2020), Turkey (Satici, Gocet-Tekin, Deniz, & Satici, 2020) and Vietnam (Nguyen et al, 2020). Most of the studies consistently found that the FCV-19S has a unidimensional factor structure.…”
Section: Introductionmentioning
confidence: 99%
“… Collectivism Morales-Rodríguez, 2021 180 4.5 Spain Europe University students 20.76 Individualism Giordani et al, 2021a 4638 7 Brazil South America General population 41.50 Collectivism Kassim et al, 2021 255 5.5 Malaysia Asia General population N.A. Collectivism Giordani et al, 2021b 387 9.5 Mozambic Africa General population 34.50 Collectivism Ahammed et al, 2021 1317 4 Bangladesh Asia University students N.A. Collectivism Yalçın et al, 2021 588 6.5 Turkey Europe General population 30.42 Collectivism Studies included in the meta-analysis for gender and COVID-19 related anxiety Magano et al, 2021 1122 10.5 Portugal Europe General population 31.90 Individualism van de Venter et al, 2021 248 N.A.…”
Section: Resultsmentioning
confidence: 99%